A importância do território na produção do sucesso escolar - Coura, Charles Abrantes (2016)
The aim of this study is to verify what the preponderant factors were that led graduates of a private Higher Education Institution to choose that particular institution to enter Higher Education. Could the socioeconomic status of these subjects, the institution location, its architectural conditions and material equipment, or even the quality of the education offered have interfered in this choice? Verifying those factors became important in order to know if there is a relation between them and the choice of the institution to attend Higher Education, once those factors may lead the subjects to academic success, here understood as graduating. Besides, we were interested in knowing what expectations they had regarding Higher Education and if they were fulfilled. For this purpose, the research starts with the hypothesis that the infrastructure of the institution investigated may be seen as a differential when choosing the institution which students join, fomenting expectations that graduating is the main way to ascend socially and economically. The data were collected through a semi-structured questionnaire and survey. With the contribution of authors Pierre Bourdieu, Rogério Haesbaert and Bernard Lahire,especially the concepts of habitus, cultural capital and territory guided the research and the analysis of the empiric data. The study results show that the socioeconomic status of the subjects is one of the preponderant factors when choosing the Higher Education institution, either by the offer of scholarships or the tuition cost, although the quality of the education this institution offers and its location are also indicated as reasons for this choice. It was also observed that the hypothesis of this research was partially confirmedes